2020
DOI: 10.18097/pbmc20206606464
|View full text |Cite
|
Sign up to set email alerts
|

Targeted drug delivery system for doxorubicin based on a specific peptide and phospholipid nanoparticles

Abstract: Doxorubicin is one of the widely known and frequently used chemotherapy drugs for the treatment of various types of cancer, the use of which is difficult due to its high cardiotoxicity. Targeted drug delivery systems are being developed to reduce side effects. One of the promising components as vector molecules (ligands) are NGR-containing peptides that are affinity for the CD13 receptor, which is expressed on the surface of many tumor cells and tumor blood vessels. Previously, a method was developed for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
(22 reference statements)
1
7
0
Order By: Relevance
“…Doxorubicin (DOX) is an antineoplastic antibiotic with wide pharmacological activity [ 2 , 3 , 7 , 24 , 31 , 34 , 35 , 36 , 37 , 38 ]. Analysis of DOX levels is an important task for the determination of this medication in body fluids for the individualization of drug dosage, and for the investigation and evaluation of the mechanism of drug–biomolecule(s) interactions [ 12 , 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Doxorubicin (DOX) is an antineoplastic antibiotic with wide pharmacological activity [ 2 , 3 , 7 , 24 , 31 , 34 , 35 , 36 , 37 , 38 ]. Analysis of DOX levels is an important task for the determination of this medication in body fluids for the individualization of drug dosage, and for the investigation and evaluation of the mechanism of drug–biomolecule(s) interactions [ 12 , 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…The NGR peptide has affinity for aminopeptidase N (known as the CD13 marker on the membrane surface of tumor cells). It was shown that the new doxorubicin derivative with NGR peptide (NPh-DOX-NGR) is able to penetrate and internalize to a greater extent in HT-1080 (CD13-positive) cells [ 24 ]. NGR peptide did not reduce anticancer activity of DOX [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several methods and tools are presently accessible to shield NPs for the active targeting of BC cells. Previously, monoclonal antibodies were employed to target epitopes on the cell surface; however, the widespread screening of peptide and aptamer archives has significantly extended the number of ligands available for targeted BC therapy [177]. Various ligands are presently employed, viz., antibodies, peptides, aptamers, oligosaccharides, and small molecules, and can precisely identify and attach to an overexpressed target on the surface of the cell [76,175,176,178].…”
Section: Ligandsmentioning
confidence: 99%
“…The inclusion of Dox in phospholipid nanoparticles contributed to its accumulation in the tumor and led to an increase in its specific activity. In subsequent experiments, the resulting Dox phospholipid composition was constructed using a targeted NGR peptide (NPh-Dox-NGR) [32]. This work is a comprehensive study of the physical properties of the Dox phospholipid composition with and without the To increase bioavailability and reduce side effects, NPs are modified with various targeted molecules: peptides [14][15][16], aptamers [17][18][19], small molecules [20][21][22], and antibodies [23,24].…”
Section: Introductionmentioning
confidence: 99%